Effects of chemical warfare agent decontaminants on trace survival: Impact on fingermarks deposited on glass. Issue 6 (23rd August 2022) - Radgen‐Morvant, Isabelle; Kummer, Natalie; Curty, Christophe; Delémont, Olivier
Abstract: Following a chemical incident involving chemical warfare agents or more broadly, chemical weapons, there are two possible approaches in dealing with the traditional forensic analysis of contaminated exhibits. The first is to analyze the contaminated items under safe conditions (i.e. in laboratories dedicated to the handling of such substances), while the second relies on item decontamination prior to processing them in traditional forensic laboratories. One of the main limitations of the latter is the possible degradation or destruction of traces caused by the decontamination process. Hence, it is crucial to have as much information as possible on the impact of different decontamination agents and procedures on traces. This research presents experimental results on the recovery of fingermarks on glass after the application of decontaminants typically used in case of chemical incidents. The impact of 11 decontaminants on fingermarks deposited on glass and on the subsequent enhancement with cyanoacrylate and Small Particle Reagent (SPR) was evaluated (by visual examination) by four evaluators. The results of the study demonstrated that the persistence of fingermarks on glass is highly dependent on the type of decontaminant used. Decontamination agents based on the principle of nucleophilic substitution to neutralize toxic chemicals allowed good subsequent development of fingermarks with SPR. Powdered decontaminants did not show any indication of alteration of fingermarks, whereas decontamination with oxidants leads to variable results.